The Relationship Between Income Inequality and the Palliative Function of Meritocracy Belief: The Micro- and the Macro-Levels Both Count - Hadarics, Márton; Kende, Anna; Szabó, Zsolt Péter (Frontiers in Psychology, 2021)
In the current paper, we report the analysis of the relationship between meritocracy belief and subjective well-being using two large international databases, the European Social Survey Program (N= 44,387) and the European Values Study Program (N= 51,752), involving data gathered from 36 countries in total. We investigated whether low status individuals are more likely to psychologically benefit from endorsing meritocratic beliefs, and the same benefits are more pronounced in more unequal societies. Since meritocracy belief can function as a justification for income differences, we assumed that the harsher the objective reality is, the higher level of subjective well-being can be maintained by justifying this harsh reality. Therefore, we hypothesized that the palliative function of meritocracy belief is stronger for both low social status (low income) individuals, and for those living in an unequal social environment (in countries with larger income differences). Our multilevel models showed a positive relationship between meritocracy belief and subjective well-being, which relationship was moderated by both individual-level income status and country-level income differences in both studies. Based on these results, we concluded that the emotional payoff of justifying income inequalities is larger if one is more strongly affected by these inequalities.